Trayectorias óptimas de inversión durante el ciclo de vida en un sistema de multifondos - Arboleda Bedoya, Alejandra (2013)
Taking into account the new Colombian multi-funds scheme of the Individual Benefits Plan, an analysis was made through the application of stochastic and actuarial tools with the purpose of determining the moment in which agents (according to their social characteristics: sex, income expectation, moment they begin to pay contributions, contribution probability) must transfer their retirement account into the different offered portfolios. Considering the profitability and the risk the agents want to assume, as key elements, it is generally observable that they must remain a great percentage of their working lives in the high-risk investment fund to achieve a greater financial capital accumulation and a greater probability to attain a reasonable replacement rate. DOI: 10.1016/S2077-1886(13)70032-5